2014
DOI: 10.1002/ppap.201400146
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, Characterization, and Comparison of Oxygen-Rich Organic Films Deposited by Plasma- and Vacuum-Ultraviolet (VUV) Photo-Polymerization

Abstract: Thin organic films with oxygen‐bearing functional groups (hydroxyl, carboxyl, …) were prepared by “co‐polymerizing” gas mixtures of ethylene (C2H4) and one of several O‐containing oxidizer molecules, O2, CO2, or N2O. This was done either by vacuum‐ultraviolet (VUV) photo‐polymerization or by low‐pressure r.f. plasma‐assisted CVD. The gas mixture ratio, R, permits one to control total oxygen concentration, [O], as well as the relative proportions of the various functionalities. Analyses were performed by XPS (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
1
18
0
3
Order By: Relevance
“…In contrast, here, when using the latter hydrocarbon, PP films yield higher [S] values, up to 48 at% (Figure b). Similar results were also reported for O‐containing films, a clear indication that the plasma‐ and VUV‐based chemistries are quite different and complex. Further, surface oxygen concentrations were always below 5 at% (results not shown), which could be an indication that these films are more stable toward aging compared to nitrogen containing films.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…In contrast, here, when using the latter hydrocarbon, PP films yield higher [S] values, up to 48 at% (Figure b). Similar results were also reported for O‐containing films, a clear indication that the plasma‐ and VUV‐based chemistries are quite different and complex. Further, surface oxygen concentrations were always below 5 at% (results not shown), which could be an indication that these films are more stable toward aging compared to nitrogen containing films.…”
Section: Resultssupporting
confidence: 84%
“…A related finding occurred when acetylene, C 2 H 2 , was used as source gas . In addition, when using C 4 H 6 , no drop in r was observed, even at higher R values; this is somewhat surprising, because r decreased substantially in previous experiments with C 2 H 4 and N‐ or O‐containing gas mixtures . In those previous works it has been shown that NH 3 , for example, acts as an etchant for organic materials, because with increasing R values atomic H is released during fragmentation, leading to a decrease in r .…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations